2019
DOI: 10.1111/ppl.13012
|View full text |Cite
|
Sign up to set email alerts
|

Responses of nitric oxide and hydrogen sulfide in regulating oxidative defence system in wheat plants grown under cadmium stress

Abstract: We conducted a study to evaluate the interactive effect of NO and H2S on the cadmium (Cd) tolerance of wheat. Cadmium stress considerably reduced total dry weight, chlorophyll a and b content and ratio of Fv/Fm by 36.7, 48.6, 26.7 and 19.5%, respectively, but significantly enhanced the levels of hydrogen peroxide (H2O2) and malondialdehyde (MDA), endogenous H2S and NO, and the activities of antioxidant enzymes. Exogenously applied sodium nitroprusside (SNP) and sodium hydrosulfide (NaHS), donors of NO and H2S,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

8
84
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2
2

Relationship

1
9

Authors

Journals

citations
Cited by 234 publications
(93 citation statements)
references
References 91 publications
(139 reference statements)
8
84
1
Order By: Relevance
“…Photosynthetic attributes are considered as sensitive indicators of abiotic stress, which can be negatively affected by heavy metal toxicity. Reduction in Chl content and gas-exchange parameters was consistent with the finding of Kaya et al (2020), who revealed that Cd-induced a decrease of those indexes in wheat plants exposed to Cd stress. Parmar et al (2013) reported that reduced Chl content in Cd-stressed plants is due to inhibited synthesis of Chl precursor (aminolevulinic acid), which is linked to the reduction of protochlorophyllide to chlorophyllide.…”
Section: Discussionsupporting
confidence: 90%
“…Photosynthetic attributes are considered as sensitive indicators of abiotic stress, which can be negatively affected by heavy metal toxicity. Reduction in Chl content and gas-exchange parameters was consistent with the finding of Kaya et al (2020), who revealed that Cd-induced a decrease of those indexes in wheat plants exposed to Cd stress. Parmar et al (2013) reported that reduced Chl content in Cd-stressed plants is due to inhibited synthesis of Chl precursor (aminolevulinic acid), which is linked to the reduction of protochlorophyllide to chlorophyllide.…”
Section: Discussionsupporting
confidence: 90%
“…Arsenic stress enhanced the proline accumulation in the soybean plants as has been reported by Choudhury, et al [38] in Oryza sativa and Siddiqui, et al [39] in Withania somnifera. The enhanced accumulation of proline and GB protects biochemical processes, promotes ROS scavenging, and maintains redox homeostasis and functions of different enzymes [40]. According to Hasanuzzaman, et al [41], proline and GB help maintain the plant antioxidant and glyoxalase systems thereby enhancing tolerance against stress.…”
Section: Discussionmentioning
confidence: 99%
“…These are the chemical messengers that interrelate with nutrients synergistically or antagonistically and play an imperative role for modulating the physiological responses that lead to salt tolerance (Fatma et al ). Particularly, nitric oxide (NO) has emerged as an ubiquitous important free radical gaseous signaling molecule involved in plant development, various physiological functions and nutrient assimilatory processes and has also been reported to improve plant tolerance to environmental stresses including salt stress, toxic metals, low and high temperature, ultraviolet (UV)‐B, ozone, excess light and various pathogens (Fatma et al , Asgher et al , Per et al , Hasanuzzaman et al , Kaya et al , ). NO plays a pivotal role in alleviating the oxidative damage and improves the antioxidant defense machinery in several salt‐affected plant species (Guo et al , Hasanuzzaman et al , Ahmad et al , , Sehar et al ).…”
Section: Introductionmentioning
confidence: 99%